2019
DOI: 10.3389/fimmu.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Regulatory T Cell Therapy in Transplantation and Autoimmunity

Abstract: Regulatory T cells (Tregs) are important for the induction and maintenance of peripheral tolerance therefore, they are key in preventing excessive immune responses and autoimmunity. In the last decades, several reports have been focussed on understanding the biology of Tregs and their mechanisms of action. Preclinical studies have demonstrated the ability of Tregs to delay/prevent graft rejection and to control autoimmune responses following adoptive transfer in vivo. Due to these promising results, Tregs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
371
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(382 citation statements)
references
References 124 publications
(144 reference statements)
10
371
0
1
Order By: Relevance
“…Animal studies indicate that Tregs play a key role in maintaining immune homeostasis and preventing autoimmunity . Furthermore, they can recognize allogeneic major histocompatibility complex (MHC) molecules and suppress allograft rejection, and are essential for the induction and maintenance of transplantation tolerance through the mechanisms of “linked suppression” and “infectious tolerance.”…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies indicate that Tregs play a key role in maintaining immune homeostasis and preventing autoimmunity . Furthermore, they can recognize allogeneic major histocompatibility complex (MHC) molecules and suppress allograft rejection, and are essential for the induction and maintenance of transplantation tolerance through the mechanisms of “linked suppression” and “infectious tolerance.”…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, they can recognize allogeneic major histocompatibility complex (MHC) molecules and suppress allograft rejection, and are essential for the induction and maintenance of transplantation tolerance through the mechanisms of "linked suppression" and "infectious tolerance." 2 Although human Tregs constitute a small proportion (5%-7%) of circulating CD4 + T cells, they are attractive candidates for immunotherapeutic purposes given that they can be isolated and expanded in large numbers in vitro without losing their immunoregulatory properties. 3 Clinical studies have demonstrated the safety of Treg adoptive transfer in graft-versus-host disease and type 1 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory T cells (CD25 + FoxP3+) have been at the forefront of new therapeutic strategies of adoptive cell transfer for a variety of autoimmune diseases [71]. Retrospective studies in patients with myocarditis with progression to DCM have shown that they shared a decreased Treg population while their Th17 population was concomitantly increased [72].…”
Section: Anti-inflammatory T Cell Subsets: Tregsmentioning
confidence: 99%
“…[ 12 ] With such versatility in modes and targets of action, immunotherapies utilizing Tregs have been extensively investigated for the treatment of autoimmunity and allogeneic transplantation. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] While this method has shown promising results in clinical trials, [ 17,18 ] ex vivo expansion of Tregs requires extremely time‐consuming and costly protocols to generate appropriate numbers of cells for clinically significant results, due to the low frequency of Tregs in human peripheral blood. [ 13,19 ] Thus, it would be advantageous to employ more targeted approaches requiring less Tregs, such as hydrogel encapsulation to provide localized immunosuppression.…”
Section: Introductionmentioning
confidence: 99%